2021
DOI: 10.1111/ijlh.13499
|View full text |Cite
|
Sign up to set email alerts
|

Immature platelet fraction over time and clinical outcomes in patients with acute myocardial infarction

Abstract: Background Immature platelets in the circulation can be measured as immature platelet fraction (IPF). Limited data exist regarding IPF during the course of an acute myocardial infarction (AMI), the association between IPF and extent of cardiac damage, and the long‐term prognostic implications of IPF in patients with AMI. Aims To examine the temporal course of IPF during the first month after AMI, the association between IPF and extent of cardiac damage, and the long‐term prognostic effect of IPF in AMI patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Based on these results, the opportunity to defer platelet transfusions that would be given when transfusion decisions are based on platelet counts only 21 . IP has also been implicated in several pathologies, such as acute myocardial injury and sepsis, and has been found to be an early predictor of worsening in severe COVID‐19 patients 22–24 . The use of IP measurement, particularly with citrated anticoagulant, could help in patients with pseudothrombocytopenia induced by EDTA anticoagulant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, the opportunity to defer platelet transfusions that would be given when transfusion decisions are based on platelet counts only 21 . IP has also been implicated in several pathologies, such as acute myocardial injury and sepsis, and has been found to be an early predictor of worsening in severe COVID‐19 patients 22–24 . The use of IP measurement, particularly with citrated anticoagulant, could help in patients with pseudothrombocytopenia induced by EDTA anticoagulant.…”
Section: Discussionmentioning
confidence: 99%
“…21 IP has also been implicated in several pathologies, such as acute myocardial injury and sepsis, and has been found to be an early predictor of worsening in severe COVID-19 patients. [22][23][24] The use of IP measurement, particularly with citrated anticoagulant, could help in patients with pseudothrombocytopenia induced by EDTA anticoagulant. This study has limitations, including the use of only one hematological analyzer and the lack of checking of platelet counts obtained with the reference.…”
Section: Evaluation Between 1 and 24 H In Edta Sample For Ipf (A) And...mentioning
confidence: 99%
“…Thus, they are suspected to be implicated in thrombosis during some pathological settings. Indeed, higher troponin levels were associated with higher IP fractions during acute myocardial injury, with a subsequent association with worse cardiac outcomes [ 24 ]. During sepsis, higher A-IPC seems to be associated with the severity and prognosis of patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated an association between high immature platelet fraction (IPF) and increased thrombotic events in patients with ACS [11–14]. Higher levels of IPF have been identified as predictors of 1-year cardiac mortality in patients with AMI [12–14]. In a recent study conducted by our group, elevated IPF levels in the first month following AMI were linked to unfavorable clinical outcomes at 1 year [13].…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of IPF have been identified as predictors of 1-year cardiac mortality in patients with AMI [12–14]. In a recent study conducted by our group, elevated IPF levels in the first month following AMI were linked to unfavorable clinical outcomes at 1 year [13].…”
Section: Introductionmentioning
confidence: 99%